OVERCOMING BULLYING AS A NECESSARY CONDITION OF SOCIALIZATION IN THE MODERN EDUCATIONAL SYSTEM - Zadoyan, A. (SUSh Scientific Proceedings, 2025)
The article discusses the issue of harm to children and the presence of bullying within the modern educational system. Among the reasons, the low level of disciplinary education at school, the social environment, and the negative family conditions of the participants were highlighted. Among the forms of bullying, physical, psychological, and social types are distinguished. The article also provides an introduction to the structural and functional components of the ―empirical‖ model, one of the pedagogical methods aimed at overcoming bullying. The article examines the results of a survey we have conducted in a number of schools. The research aims to identify the causes of bullying in modern conditions and the forms of tolerance towards this phenomenon in different schools. The aim of the article is to highlight the importance of overcoming child violence, ―bullying‖, in the modern educational system as a necessary condition for the socialization of students